2010
DOI: 10.3923/pjbs.2010.400.404
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Pseudomonas aeruginosa Drug Resistance in Tabriz Children Hospital

Abstract: Regarding the different reports about increasing drug resistance of Pseudomonas, this study was done in Tabriz Pediatric Medical Center. In a cross sectional study, during 3 years, 84 positive culture of pseudomonas were obtained from the records of microbiology laboratory. Information about the patients and pattern of drug resistance were analyzed statistically. 81.9% of patients were below 2 years of age and all of them had one or more medical intervention. Most of the positive cultures were isolated from br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…(1) Regarding neonatal risk factors, this study shows that males (56%) were more often affected by birth trauma than females (44%), similar to Sameera.T.S. (9) Regarding birth weight, this study shows its significant influence in the occurrence of birth trauma, especially those babies with birth weight more than 4kg (macrosomic babies) which is similar to Ghorashi,et.al (10),Sameera. ( 9), Stoll BJ in 2007 (2), Mcintosh in 1998(4), Tsuji in 1997 (1), Overland in 2009 .…”
Section: Discussionsupporting
confidence: 72%
“…(1) Regarding neonatal risk factors, this study shows that males (56%) were more often affected by birth trauma than females (44%), similar to Sameera.T.S. (9) Regarding birth weight, this study shows its significant influence in the occurrence of birth trauma, especially those babies with birth weight more than 4kg (macrosomic babies) which is similar to Ghorashi,et.al (10),Sameera. ( 9), Stoll BJ in 2007 (2), Mcintosh in 1998(4), Tsuji in 1997 (1), Overland in 2009 .…”
Section: Discussionsupporting
confidence: 72%
“…Fazeli et al indicated that resistance rate of P. aeruginosa against ceftazidime was 83.3%. The other study in Tabriz, Iran, declared that, 50% of P. aeruginosa strains were resistant against this group of antibiotics (14,15). In another study conducted by Hakemi-Vala, 62.95% of P. aeruginosa strains isolated from burnt wounds showed resistance against ceftazidim (16).…”
Section: Discussionmentioning
confidence: 99%
“…Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common human enzyme deficiency in the world (2) . A systematic review and a meta-analysis estimated an overall prevalence of G6PD deficiency at 4.9%, affecting 330 million people across the globe (3,4) . The global prevalence of G6PD deficiency is greater in regions that have been historically subjected to local malaria, including Africa, Asia, the Mediterranean, and the Middle East (3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and a meta-analysis estimated an overall prevalence of G6PD deficiency at 4.9%, affecting 330 million people across the globe (3,4) . The global prevalence of G6PD deficiency is greater in regions that have been historically subjected to local malaria, including Africa, Asia, the Mediterranean, and the Middle East (3,4) . Iran is among countries that report a high prevalence of G6PD deficiency, ranging from 2.28% to 30.80% (4,5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation